1996
DOI: 10.1530/jrf.0.1080041
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of normal head morphometry of stallion spermatozoa

Abstract: The heads of stallion spermatozoa were analysed by computer automated sperm head morphometry and the morphometric values of the major subpopulations of sperm heads were assessed. The criteria for normal dimensions of stallion sperm heads are proposed based on the analysis of these measurements. Semen samples were collected from 10 fertile and 10 subfertile stallions, processed by a standard method, smeared onto microscope slides and stained using haematoxylin. At least 200 properly digitized sperm heads were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 7 publications
2
41
1
2
Order By: Relevance
“…Previous studies have reported that the values depend on the staining method [4,5,15,22]. Therefore, our values were similar to or different from those in some previous studies [1,7,8,12,14]. The aspect ratios reported in the previous data were, however, independent of the staining method [1,6,7,14].…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have reported that the values depend on the staining method [4,5,15,22]. Therefore, our values were similar to or different from those in some previous studies [1,7,8,12,14]. The aspect ratios reported in the previous data were, however, independent of the staining method [1,6,7,14].…”
supporting
confidence: 52%
“…Wide variation in the size and shape of spermatozoa occurs in virtually all mammalian species, however, and an abundance of abnormalities can be found. The sperm head has been reported to be larger in semen taken from subfertile stallions than in that from fertile stallions [6,14]. The converse has also been reported [17], and variations in size of the sperm head have been attributed to the staining methods of the studies [4,5,15,22].…”
mentioning
confidence: 87%
“…Determining differences is sperm head dimensions facilitates more precise assessment of the boar's spermiogram (Severa et al 2010). Sperm head abnormalities make it possible to distinguish fertile males from boars with decreased fertility (Gravance et al 1996). Spermatozoa of boars with poorer fertilizing effectiveness have got larger and more elongated heads than those of highly fertile males (Hirai et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…An association of sperm head dimensions and male prolificacy has been reported. Spermatozoa head dimensions of males with decreased fertility differ from the head dimensions of spermatozoa of highly fertile men (Katz et al 1986, Azis et al 1998) and stallions (Gravance et al 1996, Brito et al 2007). There has also been confirmed an association of sperm dimensions and shape with ejaculate characteristics (Rijsselare et al 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Descritores Fourier com amplitude de 0 a 2 (F0, F1, F2) foram determinados para caracterização e análise da forma (Beletti e Costa, 2003;Beletti et al, 2005a;b). A simetria da cabeça espermática também foi avaliada, sendo calculada a simetria lateral (SL) e a simetria anteroposterior (SAP) (Beletti e Costa, 2003;Beletti et al, 2005a;b (Gravance et al, 1996). Em relação às características relacionadas à compactação de cromatina (CV e Dif%), os valores médios encontrados foram mais elevados que os encontrados por Beletti et al (2005a), para espermatozoides considerados normais, e mesmo em relação aos considerados anormais encontrados em touros férteis.…”
Section: Methodsunclassified